2014
DOI: 10.7314/apjcp.2014.15.17.7467
|View full text |Cite
|
Sign up to set email alerts
|

SCYL1BP1 has Tumor-suppressive Functions in Human Lung Squamous Carcinoma Cells by Regulating Degradation of MDM2

Abstract: SCY1-like 1-binding protein 1 (SCYL1BP1) is a newly identified transcriptional activator domain containing protein with many unknown biological functions. Recently emerging evidence has revealed that it is a novel regulator of the p53 pathway, which is very important for the development of human cancer. However, the effects of SCYL1BP1 on human lung squamous carcinoma cell biological behavior remain poorly understood. In this study, we present evidence that SCYL1BP1 can promote the degradation of MDM2 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Interestingly, GORAB has been linked to the regulation of TRP53 (p53) expression during neurite outgrowth ( Liu et al. , 2012 ) and tumor cell growth in vitro ( Hu et al , 2012 ; Yang et al , 2014 ), in which GORAB acts in MDM2-mediated polyubiquitination and proteasome degradation of p53 ( Yan et al , 2010 ; Zhang et al , 2005 ). While regulating p53 stability by GORAB unlikely plays a significant role during epidermal morphogenesis, it remains to be determined whether GORAB is involved in post-natal skin homeostasis by regulating the level of p53 at the post-translational level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GORAB has been linked to the regulation of TRP53 (p53) expression during neurite outgrowth ( Liu et al. , 2012 ) and tumor cell growth in vitro ( Hu et al , 2012 ; Yang et al , 2014 ), in which GORAB acts in MDM2-mediated polyubiquitination and proteasome degradation of p53 ( Yan et al , 2010 ; Zhang et al , 2005 ). While regulating p53 stability by GORAB unlikely plays a significant role during epidermal morphogenesis, it remains to be determined whether GORAB is involved in post-natal skin homeostasis by regulating the level of p53 at the post-translational level.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is an endothelial cell surface receptor that displays several functions associated with host defence [28,29]. SCYL1BP1 encodes SCY1-like 1-binding protein 1, a regulator of the p53 pathway with tumour-suppressive function [30][31][32]. API5 encodes the protein apoptosis inhibitor 5, which is reported to be a suppressor of apoptosis and to play a key role in tumour progression [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 GORAB is also implicated in bone and hair follicle formation, 3,4 neurite outgrowth, 5 sciatic nerve regeneration, 6 and tumor cell growth. [7][8][9] GORAB is expressed in the lung. 1,3,6 We found that homozygous neonates of Gorab knockout (Gorab −/− ) mouse models exhibited severe breathing difficulties and fully penetrant neonatal lethality, 3 suggesting that GORAB plays a critical role in the embryonic morphogenesis of the respiratory or the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…GORAB physically interacts with RAB6 and ARF5, and is believed to function in intracellular trafficking . GORAB is also implicated in bone and hair follicle formation, neurite outgrowth, sciatic nerve regeneration, and tumor cell growth …”
Section: Introductionmentioning
confidence: 99%